-3(2v-4)+2v=6(v+3)

Simple and best practice solution for -3(2v-4)+2v=6(v+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2v-4)+2v=6(v+3) equation:


Simplifying
-3(2v + -4) + 2v = 6(v + 3)

Reorder the terms:
-3(-4 + 2v) + 2v = 6(v + 3)
(-4 * -3 + 2v * -3) + 2v = 6(v + 3)
(12 + -6v) + 2v = 6(v + 3)

Combine like terms: -6v + 2v = -4v
12 + -4v = 6(v + 3)

Reorder the terms:
12 + -4v = 6(3 + v)
12 + -4v = (3 * 6 + v * 6)
12 + -4v = (18 + 6v)

Solving
12 + -4v = 18 + 6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6v' to each side of the equation.
12 + -4v + -6v = 18 + 6v + -6v

Combine like terms: -4v + -6v = -10v
12 + -10v = 18 + 6v + -6v

Combine like terms: 6v + -6v = 0
12 + -10v = 18 + 0
12 + -10v = 18

Add '-12' to each side of the equation.
12 + -12 + -10v = 18 + -12

Combine like terms: 12 + -12 = 0
0 + -10v = 18 + -12
-10v = 18 + -12

Combine like terms: 18 + -12 = 6
-10v = 6

Divide each side by '-10'.
v = -0.6

Simplifying
v = -0.6

See similar equations:

| 22/b=11/3 | | -18X-129=-9X-84 | | -6X+14=-4X+8 | | 4g+3=1 | | -21X-75=-14X-47 | | 2x+3x^2=4 | | 10X+81=5X+51 | | 17X-72=11X-48 | | 3(w-7)-6=-3(-9w+7)-9w | | -21X-217=-12X-136 | | -12X-217=-12X-136 | | -11X-9=-7X-5 | | -19X-51=-12X-30 | | 8x-12=20x | | (2x+75)=(4x-25) | | 1+2(5x-3)=-2(6x-5)+4x | | (4x+18)=(7x-72) | | 4t^2-14t+35=0 | | -3X+7=-2X+4 | | 3/8*x=21/2 | | 4g+3=1g | | 3-2x=1000x | | 37w^2-312w-192924=0 | | (82.4-52)3/5=x | | -5X+13=-3X+7 | | (84.4-52)3/5=x | | z+72=8 | | 21X-39=13X-23 | | -11X-85=-6X-45 | | 6X-43=3X-22 | | 12X+134=6X+80 | | 3ln(x)+8=ln(3x)+12 |

Equations solver categories